LINGKUNGAN HIDUP SEBAGAI SUBJEK HUKUM: REDEFINISI RELASI HAK ASASI MANUSIA DAN HAK ASASI LINGKUNGAN HIDUP DALAM PERSPEKTIF NEGARA HUKUM - Usman, Abdurrahman Supardi (Legality : Jurnal Ilmiah Hukum, 2018)
Inspired by â€œShould Trees Have Standing? Toward Legal Rights for Natural Objectsâ€ (Christopher D. Stone, 1974) that popularized the doctrin: â€œenvironment as a legal subjectâ€. This thesis was directly elaborating the relation between the constitutional aspect of the â€œstate of lawâ€ and its admission of environmental rights, not just about the dimention of the philosophy of law but beyond of it: this thesis was discuss about the theoretical dimention of law and its relevance in Indonesia. At least there are two monumental cases in the world which were become the landmark case of environmental disputes resolution based of by the doctrin of ecocracy. In the dissenting opinion of the judge William O. Douglas in Sierra Club vs Mortonâ€™s case, United Stated of America (1972) and in the appeal decision of the Wheeler vs the Government of the provincial of Rojaâ€™s case, Ecuador (2011). Those cases had opened a new perspective in the legal proceeding that the environment had be approved as a legal person. In other words, the environment had recognized as a legal subject. Then, by using the conseptual approach and comparative of law approach, this thesis had elaborated the relevance of this doctrin: â€œThe Environment as a Legal Subjectâ€ in Indonesian context then verified it with the related legal theories. Besides it all, in this thesis also discuss the relation between of the environmental legal protection and the state of law concept in the ecocracy and constitualism perspective framework. Hopefully this thesis would be the steping stone to realize the constitutionalisation the environment rights and to realize the legal standing innovation in the environmental disputes resolution.